The teaching of English phonetics through the Jolly phonics method; to contribute for a better pronunciation. - Llerena Valverde, Sonia Gabriela (2023)
The research project entitled "Teaching the phonetics of English through the Jolly Phonics method to contribute to a better pronunciation" was carried out with the general objective of analyzing the effectiveness of the application of the Jolly Phonics method for teaching English phonetics; to contribute to a better pronunciation at Primer año de la Escuela Particular de Educación General Básica San Pedro de Guamote. It presents a quantitative scope of a descriptive-applicative nature. Likewise, it integrates a bibliographic review of concepts focused on developing the Jolly Phonics methodology. Additionally, a Rubric was developed to know the level of knowledge in the students at Primer año de la Escuela Particular de Educación General Básica San Pedro de Guamote about phonemes and graphemes before and after the application of the Jolly Phonics method of the population made up of 17 first-year students of Basic General Education of the selected educational institution. Through this instrument, it was evaluated how students acquired pronunciation in the English language. In addition, during the training, other activities were applied, such as worksheets on the seven phonemes groups, flashcards with images and words, songs, and tricky words own of the Jolly Phonics method, to improve the pronunciation of this group of students. The results indicated that before implementing the learning of the Jolly Phonics method, the first-grade students had little knowledge of the English language and of factors such as the pronunciation or phonetics of the sounds of the English language. Subsequently, by implementing the teaching of the Jolly Phonics method the students had a better level of pronunciation of the English language. In addition, the students developed skills in reading and writing where they put into practice what they learned. However, since the literacy process is progressive, it is recommended to continue with the constant training of this method.